The effect of small-sided games and HIIT formats and competitive level on enjoyment and exercise intensity in young adult male soccer players - Xu, Weiqiang; Trybulski, Robert; Silva, Rui Miguel; Zhao, Yichen; Castro, Henrique de Oliveira; Costa, Gustavo de Conti Teixeira; Clemente, Filipe (Biology of Sport, 2025)
This study aims to analyze the differences in Physical Activity Enjoyment Scale (PACES) scores and exercise intensity across small-sided games (SSGs) and high-intensity interval training (HIIT) formats among soccer playersfrom Tier 2 and Tier 3 competitive levels. Utilizing a cross-sectional design, 77 male players(20.64±1.56 years) participated in four training sessions under controlled conditions. Enjoyment was assessed with PACES, while exercise intensity was monitored through heart rate and rating of perceived exertion (RPE). The training formats included 1v1 and 5v5 SSGs and long and short HIIT formats. Players were categorized as Amateur (Tier 2) or Competitor (Tier 3) based on training volume and performance level. The training formats included 1v1 and 5v5 SSGs and long and short HIIT formats. The present study revealed significant differences in PACES scores across the different training formats ( p < 0.001), with the 5v5 format yielding the highest scores and long HIIT the lowest. A significant interaction between training format and competitive level was observed ( p = 0.011). Tier 2 players reported higher PACES scores in the 5v5, 1v1, and Short HIIT formats compared to Tier 3 players. SSGs and HIIT formats significantly influence enjoyment, with smaller-sided formats (1v1) and short HIIT showing the highest enjoyment levels. Tier 2 players reported higher enjoyment and physical efforts than Tier 3 players, in 5v5, 1v1, and short HIIT formats. These findingsshow the importance of programming training sessions according to the competitive level of athletes to maximize enjoyment and manage effort in soccer training programs.